If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -7) = -9 Reorder the terms: 3(-7 + 2x) = -9 (-7 * 3 + 2x * 3) = -9 (-21 + 6x) = -9 Solving -21 + 6x = -9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 6x = -9 + 21 Combine like terms: -21 + 21 = 0 0 + 6x = -9 + 21 6x = -9 + 21 Combine like terms: -9 + 21 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| 12+-3x=-7x-48 | | 7x+10+5x-8x= | | 6x+33=14x-63 | | 6q+5q= | | -3q=5 | | (5x-22)(2x+35)= | | -8.4=c-3.1 | | 4.4=c+0.7 | | z^2+27=12z | | 7x^2+6x-2=0 | | x^2+27=12z | | 7q-5=10q+19 | | 3x+5-2=2x+12 | | 3p+5=j | | (2x+1)(4x^2+27x-7)=0 | | 10(x-4)=8x-32 | | 4x^2+32x=192 | | .5(h+5)(h)=18 | | 2x^3+6x=-7x^2 | | 6(b-4)=30 | | 25=.5(h*h+8) | | (-11x^2y^2)(-6xy^5)= | | 6x^2+17x+7= | | 3a^3-36a^2+81a=0 | | 3x^2+7X-15=0 | | (3x)(-2x^5)= | | 4x^0y= | | 6(6x-7)(3x+7)=0 | | -37+(-48)=d | | 9y-4x=12 | | -8(x+3)=8-7x | | 4m^2+7m=25 |